1987
DOI: 10.1002/sia.740100405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the alloying elements Ti, Nb, Mo and V on the grain boundary segregation of P in iron and steels

Abstract: Investigations have been performed on the effects of the alloying elements Ti, Nb, Mo and V on the grain boundary segregation of phosphorous in iron and steels. The methods are AES analysis of grain boundaries on intergranular fracture faces and field-ion microscopy and mass spectrometry (atomprobe). The elements Ti and Nb show strong interaction with P, keeping P in the grain and decreasing its grain boundary segregation. In the alloys and steels containing carbon, Ti and Nb react under formation of carbides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…As a matter of fact, complex multiphase particles involving P and Mo have been observed to form upon ageing in our &-P-Mo alloys [1,39]. Also, an alternative trapping mechanism of P atoms in the stress field of MQC precipitates has been observed by APHM [34,40]. However, although it may be an interesting contribution in specific cases, this mechanism is not able to explain all cases of reduction in P segregation by Mo [I].…”
Section: Ternary Attractive Co-segregationmentioning
confidence: 97%
“…As a matter of fact, complex multiphase particles involving P and Mo have been observed to form upon ageing in our &-P-Mo alloys [1,39]. Also, an alternative trapping mechanism of P atoms in the stress field of MQC precipitates has been observed by APHM [34,40]. However, although it may be an interesting contribution in specific cases, this mechanism is not able to explain all cases of reduction in P segregation by Mo [I].…”
Section: Ternary Attractive Co-segregationmentioning
confidence: 97%
“…Niobium has been found to decrease phosphorus segregation in iron. 25 It was proposed that this decrease occurred by the formation of Nb-P clusters in the matrix, as no precipitates were detected. Therefore, we wanted to determine if niobium would also decrease phosphorus segregation in austenitic stainless steels.…”
Section: Segregation Of Phosphorus In a Niobiumcontaining Steelmentioning
confidence: 99%
“…14) It has also been found that Nb had a repulsive interaction with P, when it segregated at the grain boundary of γ -phase. 15) In addition to the interaction between trace amounts of Nb and P during the quenching and tempering of high-carbon steel, if the harmuful effect of P on the precipitation of C during LTT 5) can be alleviated by adding trace amount of Nb, it might be useful suggestions for improving the properties of high-carbon steel used for knitting needles, and useful hints for understanding the LTT behavior of high-carbon martensite.…”
Section: Introductionmentioning
confidence: 99%